Problematika pendidikan di Indonesia - Widyastuti, Afidatul Azizah Rena (Maliki Interdisciplinary Journal, 2024)
This scientific work deals with the problems of education in Indonesia. The problem of education in Indonesia is an issue that continues to be a major concern in efforts to improve the quality of education. This article outlines some of the major problems facing the Indonesian education system and tries to present possible solutions. Some of the problems that have arisen are incompatibility of curricula, lack of qualified educators, and inadequate facilities and infrastructure. Facing this problem requires collaboration between governments, schools, communities, and the private sector. Increased education in Indonesia will require strong commitment, structural change, and sustainable investment. Awareness of the importance of quality education as the engine of national development must be continuously pursued in order to a brighter future for the young generation of Indonesia.